Sosialisasi Dan Pelatihan Pembuatan Pupuk Organik Cair Berbasis Limbah Tanaman Di Desa Ubung Kabupaten Lombok Tengah - Kurniasih Sukenti; Nur Indah Julisaniah; Rina Kurnianingsih; Sukiman Sukiman (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
Abstract. Several problems related to the use of chemical fertilizers are fertilizer prices that continue to increase, in certain situations there is a shortage of fertilizers and continuous use can reduce the population of soil microorganisms. The purpose of this community service activity is to provide counseling and training on the manufacture of liquid organic fertilizer from plant waste using EM4 activator to the youth of Ubung Village, Jonggat District. The method of activity is lectures and practice of making liquid fertilizer, harvesting fertilizer products and packaging. The activity has been carried out in accordance with the plans and stages that have been set, and liquid fertilizer has been produced which is packaged in plastic bottles. The physical characteristics of the liquid fertilizer produced after 20 days of the fermentation process showed results that met the criteria as a good liquid organic fertilizer, namely temperature 28oC, pH 4, brownish yellow color and smelled of tape. Liquid fertilizer has been distributed to target residents and used as plant fertilizer. Through this activity, the youth of Ubung Village who are participants have succeeded in making liquid organic fertilizer based on plant waste and have applied it as fertilizer to their plants. Keywords: liquid fertilizer, plant waste, organic, EM4